The Future of Swiss Hospital Capacity Planning - New impulses from real-world evidence and stakeholder inputs - Justus Vogel; Enqi Fu; Charlotte Lang; David Ehlig; Alexander Geissler (University of St.Gallen, School of Medicine, Chair of Health Economics, Policy and Management, 2026)
Acute somatic hospital care accounts for a major share of Swiss healthcare expenditures. Reports of hospital deficits have increased in recent years, making them a major concern for health policy. These two factors raise questions about the adequacy of the hospital landscape and inpatient service provision, especially regarding the efficient utilization of human resources and infrastructure. Care planning is an important lever for efficient service provision. From 2012 onwards, all cantons have adopted Zurich's Hospital Capacity Planning Model (HCPM), which allocates service mandates to hospitals based on hospital planning service groups (SPLGs), complemented by national regulation on inter-cantonal planning of highly specialized medicine (IVHSM). Despite these reforms, current planning still insufficiently reflects actual patient flows across cantons and does not integrate inpatient and outpatient need for care. This study provides empirical evidence and impulses to inform the future development of hospital - and more broadly - care planning in Switzerland. The research questions (RQs) are: (1) To what extent does current cantonal hospital planning align with real-world patient flows and service mandate utilization? (2) How should SPLGs be allocated to different regional planning levels, considering complexity and urgency? (3) What are health system stakeholders' priorities for care planning (e.g., inter-cantonal planning, inter-sectoral planning)?
Keywords: I18; 330; Hospital Capacity Planning; Health Policy Design; Real-world Evidence; Health Policy Reform